2020
DOI: 10.3390/cancers12040835
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Sporadic and NF2-Related Vestibular Schwannoma

Abstract: Vestibular schwannoma (VS) is a benign primary brain tumor that occurs sporadic or as part of a genetic syndrome. The most common cause is the mutation of the NF2 tumor suppressor gene that is involved in the production of the protein merlin. Merlin plays a role in cell growth and cell adhesion. In patients with NF2, the VSs arise bilaterally and coincide with other brain tumors. In sporadic VS, the tumor is typically unilateral and does not coincide in combination with other tumors. MRI is the standard imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 143 publications
0
24
0
Order By: Relevance
“…Nowadays, we know that each treatment decision in NF2 disease requires a complete evaluation of all cranial and spinal locations of the disease in order to establish surgical priorities and strategies. Yao et al already stated in case of vestibular schwannomas, that preferred management is surgery followed by radiation, depending on institutional protocols [ 34 ]. They also reported that management for medium- or small-sized vestibular schwannomas may include wait and watch, radiotherapy and/or surgery regarding to the patients’ preference or also the institutional standards.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nowadays, we know that each treatment decision in NF2 disease requires a complete evaluation of all cranial and spinal locations of the disease in order to establish surgical priorities and strategies. Yao et al already stated in case of vestibular schwannomas, that preferred management is surgery followed by radiation, depending on institutional protocols [ 34 ]. They also reported that management for medium- or small-sized vestibular schwannomas may include wait and watch, radiotherapy and/or surgery regarding to the patients’ preference or also the institutional standards.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiotherapy was associated with better facial nerve function, hearing preservation and quality of life. A cohort study compared the outcomes of stereotactic radiotherapy and surgery in vestibular schwannomas with a tumor diameter ≤ 2.8 cm with no differences observed in terms of functional outcomes, tumor control and mortality [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This Special Issue is completed with two reviews. Our group gives an up to date overview with modern day treatment strategies for sporadic and NF2 related VS. One clear point we tried to make is that the management strategy has shifted towards preserving function as longs as possible in combination with tumor control [ 9 ]. The other review by Lee et al focuses on the loss of Merlin/NF2 in meningioma biology.…”
mentioning
confidence: 99%